TRANSFORMATION OF CONTEMPORARY ISLAMIC LEGAL THINKING IN RESPONDING TO THE CHALLENGES OF TRADITION, MODERNITY, AND GLOBALIZATION - Taslim Jusmin; M.Airil Ahmadi; Kurniati Kurniati (ANAYASA : Journal of Legal Studies, 2026)
The rapid development of global society, characterized by accelerating modernity and the expanding influence of globalization, poses significant challenges to the relevance and application of Islamic law. On the one hand, Islamic law is deeply rooted in the normative and textual tradition of classical fiqh; on the other hand, contemporary social realities demand legal responses that are adaptive, contextual, and oriented toward justice. This tension between tradition and change highlights the urgent need for a transformation of contemporary Islamic legal thought that preserves the normative legitimacy of the sharīʿah while responding effectively to modern challenges. This study aims to analyze the transformation of contemporary Islamic legal thought in addressing the challenges of tradition, modernity, and globalization, as well as to examine the normative framework that enables such transformation. The research employs a normative juridical method, using conceptual, philosophical, and statutory approaches by examining the Qur’an, Sunnah, principles of maqāṣid al-sharīʿah, and relevant national legislation. The findings indicate that Islamic law possesses inherent flexibility that allows for legal reconstruction through ijtihād, textual reinterpretation, and the strengthening of a maslaḥah-oriented approach. This transformation enables Islamic law to function as a living law capable of harmonizing with national legal systems and global values without losing its normative identity. Consequently, contemporary Islamic legal thought plays a crucial role in promoting a responsive, just, and public interest–oriented legal framework.